Perancangan Sistem Infomasi Penjualan Berbasis Website CV Jaya Agung Jakarta Barat - Mohamad Fikriyansah Taba; Popon Handayani (STMIK Pringsewu, 2022)
Technology today is growing so rapidly, especially in the field of information technology. It is a natural thing for people who live in today's technological era, CV. Jaya Agung is a company engaged in the trading industry, especially the sale of spare parts for four-wheeled vehicles, CV. Jaya Agung is located at Jl. Daan Mogot KM 14 No.14, Cengkareng Barat, West Jakarta 11730. At this time the CV system. Jaya Agung is still done manually, which is still done by recording and there is no sales report per period, and doing every customer spare part sales transaction who comes to the CV store. Jaya Agung. With this research, it is hoped that the creation of a website-based sales media using the Waterfall method, with this system aims to facilitate the sales transaction process of CV. Jaya Agung to make it easier and customers do not need to come to the store. Provide complete information regarding spare parts information.